Confronting premature death: Cluny, Arthur Kingsley Porter, and the tomb of Alfonso Ansúrez. Issue 4 (2nd October 2021) - Lastra, Elizabeth
Abstract: Since the early twentieth century, the carved sarcophagus of Alfonso Ansúrez has been considered a central work of Spanish medieval art. Nonetheless, its singular imagery remains enigmatic and its contentious modern history largely unexplored. The late eleventh-century sarcophagus of the young noble Alfonso Ansúrez is both exceptionally clear and frustratingly enigmatic. Inscriptions label every detail, down to a cup labeled calix, and large carved figures signal the viewer through pronounced gestures, but the tomb's details diverge from developing norms in funerary iconography. Unlike the common medieval representation of the deceased as a nude androgynous soul, the young Alfonso, while plainly identified by the inscription "deceased Alfonso, " is shown fully dressed and animate. This article argues that the tomb depicts Alfonso's reception of last rites, which may not have been observed before the young noble's untimely death. The carefully marked details actualize a ritual indispensable for the salvation of his soul. The article also elucidates the little-known role played by Arthur Kingsley Porter — probable victim of another premature death — in the Spanish monument's clandestine and controversial appearance in the United States.